Morphological characterization and clinical effects of stromal alterations after intracorneal ring segment implantation in keratoconus - Hamon, Loic; Schlötzer-Schrehardt, Ursula; Flockerzi, Fidelis A.; Seitz, Berthold; Daas, Loay (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: To analyze the histological and (ultra)structural stromal tissue changes after femtosecond (Fs) laser–assisted intracorneal ring segment (ICRS) implantation and their refractive and topographic effects in patients with keratoconus. Methods: This monocentric retrospective case series included 15 consecutive patients with clinical peri-segmental lamellar channel deposits after treatment with Fs-ICRS implantation for keratoconus. The stromal changes were investigated using in vivo confocal microscopy. Two patients underwent a penetrating keratoplasty after the Fs-ICRS implantation; the explanted corneas were processed for histopathology and transmission electron microscopy (TEM). Refractive and topographic effects were investigated comparing the uncorrected (UDVA) and corrected (CDVA) distance visual acuity, spherical equivalent (SE), flat (K1), steep (K2), and steepest (Kmax) keratometry before and after detection of lamellar channel deposits. Results: In vivo confocal microscopy revealed diffuse linear and focal granular hyperreflective structures. Histologically, there was mild proliferation of fibroblasts and fibrosis. TEM demonstrated focal accumulations of degenerated keratocytes with cytoplasmic lipid inclusions. There were no significant changes for UDVA (Δ = 0.0 ± 0.2 logMAR; p = 0.67), CDVA (Δ = 0.0 ± 0.1 logMAR; p = 0.32), SE (Δ 0.1 ± 0.9 D; p = 0.22), K1 (Δ = 0.3 ± 1.0 D; p = 0.28), K2 (Δ = 0.1 ± 0.9 D; p = 0.51), and Kmax (Δ = 0.3 ± 1.5 D; p = 0.17). Conclusions: Two types of structural stromal changes were identified: (1) diffuse peri-segmental fibrosis and (2) lamellar channel deposits. These structural changes showed no evidence of a relevant refractive or topographic effect.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Intracorneal ring segments; Keratoconus; Lamellar channel deposits; Peri-segmental fibrosis; Ultrastructural changes